Tehniško izobraževanje in inženirska pedagogika - Aberšek, Boris; Flogie, Andrej (University of Maribor Press, 2019)
Technical Education and Engineering Pedagogy. In technical/engineering education, students are taught how to understand technology in its social, economic and ecological contexts. In this process, it is particularly important to teach them about the historical aspects of technology, as well as its most recent technological advancements. In the classroom, students should be motivated for active and independent learning mostly through the learning while working principle. In order for technical education to be successfully realized in such an active way, its focus needs to shift from instruction (i.e., passive learning) to active learning. We assume that the content and interpretations of this book will often differ from the existing ideas rooted among both teachers and students. We hope that the presented ideas will arouse cognitive dissonance, mental discomfort in teachers, which will challenge them to review and reassess the "theories inside their heads"; as for the students, we hope that this book will lead them to the discovery of an easier and more effective way to acquiring the required and necessary knowledge. This book is intended for both, teachers of technical subjects, as well as students, so that by understanding the process of learning they will be able to acquire knowledge more easily and more thoroughly.